Ataxia, intentional tremor and hypotonia syndrome caused by a novel POU4F1 gene mutation: a case report - Hu, Qisheng; Zhu, Feng; Wang, Wanfen; Xu, Yihang; Ren, Haiyan; Zheng, Yanni; Jiang, Yiqing; Ke, Shaofa (Frontiers in Genetics, 2025)
Childhood-onset ataxia, intention tremor and hypotonia syndrome (ATITHS) is a rare neurological disorder that encompasses features of hereditary ataxia, hypotonia. To date, only one report has associated the pathogenic variant in the POU4F1 gene with ATITHS. We report the case of a 28-year-old male who presented with lifelong gait instability and hypokinesia. The brain magnetic resonance imaging of this patient revealed significant cerebellar atrophy. Genetic analysis identified a novel heterozygous nonsense variant in Pou structural domain class 4 transcription factor 1 (POU4F1), which is predicted to result in loss of normal protein function. Segregation analysis within the family confirmed the presence of this variant in multiple symptomatic relatives. We confirmed diagnosis of ATITHS for this patient. This report provides additional evidence linking this mutation to specific neurologic disorders. We emphasize the importance of genetic testing to determine genetic etiology in patients presenting with ATITHS.